Selecting a discrete multiple criteria decision making method for Boeing to rank four global market regions. (April 2020) - Haddad, M.; Sanders, D.; Tewkesbury, G.
Abstract: This work describes the creation of a new method to choose a suitable Multi-Criteria Decision Making (MCDM) method for a Boeing strategic decision. The decision involved four global market regions being ranked based on their market attractiveness and competitive strength when risk and uncertainty were anticipated. Following an analysis of MCDM problems and methods, a new organized approach was created to provide a decision maker with a sub-group of suitable MCDM methods. Sensitivity analysis was used to investigate the robustness of the outputs from the various candidate methods. A MCDM method is recommended automatically. The recommended candidate method is the one that provided the most robust output (solution to the problem). Only methods that deal with a discrete set of choices were considered. In the Boeing strategic decision presented in this paper, two MCDM methods were compared and a recommendation was made after calculating the minimum percentage change in performance measures and criteria weights required to change the ranking of any two alternatives. An MCDM method was recommended based on a compromise between the minimum percentage change that was required in the inputs to change the ranking of alternatives. Some propositions are discussed based on general scenarios concerning MCDM problems.